Home-Based Transabdominal Interferential Electrical Stimulation for Six Months Improves Paediatric Slow Transit Constipation (STC) - Yik, Yee Ian; Hutson, John; Southwell, Bridget (Wiley, 2017)
Background: Transcutaneous electrical stimulation (TES) for one to two months has produced some improvement in treatment-resistant slow-transit constipation (STC) in children. Optimal parameters for treatment are not known. It is possible that more improvement would occur with stimulation for longer. This study examined the effectiveness of stimulation for six months. Methods: Children with STC confirmed by nuclear transit study (NTS) were enrolled prospectively. All had chronic constipation for greater than two years and had failed medical treatment. TES was performed for one hour/day for six months using the INF 4160 (Fuji Dynamics) portable stimulator and 4 cm × 4 cm electrodes near the belly button and on the back. Families kept bowel diaries and completed PEDSQLCore QOL (4.0) questionnaires before and at end of treatment. Results: Sixty-two children (34 females; seven years, 2–16 year) with STC were studied. Defecation frequency increased in 57/62 (91%, mean ± SEM pre- 1.49 ± 0.20 vs. post- 3.25 ± 0.25 defecation/week, p < 0.0001) with the number with ≥3BA increasing from 6 to 37 (10–59%). Soiling frequency decreased from 4.8 to 1.1 days/week (p <0.001). Abdominal pain decreased from 1.7 to 0.3 days/week (<0.0001), and spontaneous urge to defecate improved. Quality of life (p < 0.01), mean transit index and gastric emptying on NTS improved (p < 0.005). Conclusion: Treatment-resistant STC responds to TES using interferential current across the abdomen when given daily for many months. Battery operated stimulators allowed stimulation at home for an hour each day. Stimulation for six months produced clinically significant improvement in defecation frequency, soiling, abdominal pain, urge to defecate, and quality of life in half of these chronic patients.